Nematicons in twisted liquid crystals - Laudyn, Urszula A.; Kwaśny, Michał; Jaworowicz, Katarzyna; Rutkowska, Katarzyna A.; Karpierz, Miroslaw A.; Assanto, Gaetano (Photonics Letters of Poland, 2009)
In this work we demonstrate the properties of spatial solitary waves (nematicons) in a twisted nematic liquid crystalline film. Such self-trapped beams were created due to optical reorientation nonlinearity for a light power of a few tenths of milliwats at the distances of a few millimeters. Additionally, it was demonstrated that a weak signal beam can be guided in a channel formed by a nematicon. Full Text: PDF References: F. Simoni, "Nonlinear Optical Properties of Liquid Crystals", World Scientific Publ.: London (1997) M. A. Karpierz, "Soliton Driven Photonics", eds. A. D. Boardman and A. P. Sukhorukov (Kluwer Academic Publishers: Dordrecht 2001), p. 41. [CrossRef] G. Assanto, M. Peccianti, C. Conti,"Nematicons: Optical Spatial Solitons in Nematic Liquid Crystals", Opt. Photon. News 14, 44 (2003) [CrossRef] M. A. Karpierz, M. Sierakowski, M. Świłło, T. R. Woliński, Mol. Cryst. Liq. Cryst. 320, 157 (1998) [CrossRef] M. A. Karpierz,"Solitary waves in liquid crystalline waveguides", Phys. Rev. E 66, 036603 (2002) [CrossRef] M. Peccianti, A. De Rossi, G. Assanto, A. De Luca, C. Umeton, I. C. Khoo, "Electrically assisted self-confinement and waveguiding in planar nematic liquid crystal cells", Appl. Phys. Lett. 77, 7 (2000) [CrossRef] M. Peccianti, G. Assanto,"Signal readdressing by steering of spatial solitons in bulk nematic liquid crystals", Opt. Lett. 26, 1690 (2001) [CrossRef] M. Peccianti, G. Assanto, "Nematic liquid crystals: A suitable medium for self-confinement of coherent and incoherent light", Phys. Rev. E 65, 035603 (2002) [CrossRef] M. A. Karpierz, K. A. Brzdąkiewicz, Q. V. Nguyen, Acta Phys. Polonica A, 103, 169 (2003) K. Jaworowicz, K. A. Brzdakiewicz, M. A. Karpierz, M. Sierakowski, Mol. Cryst. Liq. Cryst. 453, 301 (2006) [CrossRef] M. A. Karpierz, Acta Phys. Polonica A, 99, 161, (2001)